Activities of the architect and artist I. S. Stepanov on Sakhalin Island - Bazilevich, Eugene (project baikal, 2023)
The article reflects intermediate results of the research project “Architects and Engineers of Eastern Outskirts of Russia (Second Half of XIX – Beginning of XX Century)”. On the basis of archival material obtained from the Russian State Historical Archive of the Far East (RSHA FE), the author describes the creative and professional activities on the island of Sakhalin performed by Ivan Stepanovich Stepanov, a graduate of the St. Petersburg Imperial Academy of Fine Arts, architect and artist.